Modification and evaluation of automated drip irrigation system - ARJUN PRAKASH K. V; Dr. Sajeena S (Guide) (Tavanur 2016 DEPARTMENT OF LAND & WATER RESOURCES AND CONSERVATION ENGINEERING)
Automated drip irrigation system consists of conductive and capacitor type sensors for the soilmoisture measurement which allowed irrigating each bed according to the requirment. It composed of water sensors, solenoid valves, microcontroller unit and LCD display. operated with GSM modem
Modification and evaluation of automated drip irrigation system